Precipitation and Land Cover Change in Komodo National Park During El Nino and La Nina - Resti Salmayenti; Putri Alya Mukti Ramadhanti (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Komodo National Park is located in East Nusa Tenggara province which has a dry tropical climate. Air temperature in this area is relatively high with a lower rainfall compared to most of other Indonesian regions. This condition causes ecosystem in Komodo National Park to be unique with a wide area of savannah and dryland forest. This study aims to identify the change of rainfall and land cover in Komodo National Park in 2018-2020. The analysis was conducted using secondary data from observations and satellite products. The result shows that West Manggarai is classified in Aw climate type. The value of rainfall follows the pattern of ENSO events with a correlation between tree-month data of rainfall and the Ocean Nino Index (ONI) is 42% in average of June-December. The land cover of vegetation in March/April has decreased by 2,240 Ha (2018-2019) and 2,517 Ha (2019-2020) or around 4% and 5%​​ of total area. La Nina has occurred during wet season 2017/2018 followed by El Nino in the coming years. There was decreasing of rainfall during November-February period in 2019 and 2020, which was 17% and 37% lower compared to 2018.